MR-Imaging of Meniscal Substitution. Issue 1 (19th November 2016) - De Coninck, Tineke; Verdonk, Peter; Verstraete, Koenraad
More than a century ago, the menisci were considered to be the functionless remains of a leg muscle. Gradually the usefulness and function of the meniscus was investigated and proven, and the link between total meniscectomy, radiographic osteoarthritis and reduced knee function was made. Subsequently, partial meniscectomy was introduced in the clinical practice. However, the frequency of symptomatic knee osteoarthritis was not substantially lowered. Therefore, meniscal repair was introduced for younger individuals with traumatic meniscus lesions with a good healing potential. Later on in the development process, the quest for meniscal replacement strategies arose. The introduction of allogenic, xenogenic and artificial materials followed in research and clinical settings. Nowadays, a lot of research is conducted on meniscal substitutes, because meniscal injuries are a very common problem in the general population. The imaging of the meniscus is running parallel to this evolution. With the development of magnetic resonance imaging (MRI), the meniscus could be perfectly visualized. A lot of studies were published on imaging of the normal meniscus, and subsequently meniscal pathology on MRI was investigated. In the current literature, a growing number of papers describe the MRI findings in artificial meniscus replacements.